Penyuluhan Masyarakat Tentang Dagusibu Dalam Meningkatkan Kesadaran Pengguna Obat Yang Rasional Di Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai Sumatera Utara - M. Gunawan; Masni; Enny Fitriani; Jarmaini Agustina; Lintang Indah Kartini; Madison Imam Mahdi (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Women in Bingkat Village play roles as housewives and are actively involved in agricultural, social, and religious activities. However, their knowledge regarding proper drug management remains limited. This program aims to improve community understanding of the DAGUSIBU concept (Get, Use, Store, and Dispose of medicines properly). The method used is assistance through counseling and education on how to obtain appropriate medicines, use them according to instructions, store them correctly, and dispose of them safely. The results indicate an improvement in community knowledge regarding rational drug management. This program is expected to increase public awareness of safe medicine use and support family health.